Gendered barriers to formal healthcare utilization: Modelling healthcare demand in a lowresource setting - Elisa Cavatorta; Wendy Janssens; Alice Mesnard (Tinbergen Institute, 2021)
This paper develops a model of healthcare demand to study healthcare choices in resourcelimited settings with poor health indicators, especially for women. Using data from rural Nigeria on individual illnesses and injuries as well as the entire portfolio of locally available providers, we estimate the effect of price, distance and quality on access to care, focussing on the heterogeneous responses to these three factors by gender. We find that women are more price sensitive than men, in particular in households where they have low bargaining power, while being equally responsive to quality or distance. Using our model to simulate ex-ante the impacts of price interventions, we predict that a full price subsidy in public clinics would substantially increase both men's and women's access to formal care, and almost eliminate the observed gender gap in formal healthcare utilization. Subsidizing both public and private clinics only marginally improves overall access, but it fully eliminates the observed gender gap in addition to broadening the capacity of the health sector to respond to increased demand when public facilities have limited capacity.
Keywords: C35; D13; I12; I13; I18; 330; Universal health coverage; healthcare provider choice; gender heterogeneity; intra-household bargaining; price endogeneity